INDONESIAN TERRORIST, ISIS, AND GLOBALIZATION OF TERROR: A PERSPECTIVE - Herdi Sahrasad (AHKAM : Jurnal Ilmu Syariah, 2018)
Terrorism has been critical issues in Indonesia. Latest, Santoso, a frontman of terrorists based in Poso, central Sulawesi, can be terminated.  His  radical adventures in Poso and East Indonesia has inspired many youths to follow  his bloody road  in an effort to carry out holy war against the secular democracy in Indonesia. In pursuit Santoso, the battle between security forces and terrorists often happens in the field.  Santoso group are part of the radical Islamist networks in Southeast Asia,  and their  imagined solidarity  with  the Middle East radical Islamists are relatively strong. So that the military help the police to combat terrorism in Indonesia.